(untitled) (Global Journal of Human-Social Science, 2018)
Canterbury basin covers an approximate area of 40 000 km2 Canterbury basin is largely an offshore basin extending slightly onshore southward across Canterbury plains and to the Southern Alps This work aimed to correlates seismic sequences boundaries earlier interpreted with sedimentary sequence surfaces observed in cores recovered from the four sites drilled across the shelf by expedition 317 This work utilises well data obtained from Integrated Ocean Drilling Program IODP expedition 317 The expedition which targeted stratigraphic seismic sequences earlier interpreted from the seismic data acquired on the eastern margin of the south island of New Zealand offshore Canterbury Three synthetic seismograms were created from well U1351B U1353C and U1352B which both contain sets of sonic and density logs at variable length this is to provide a direct means of comparison between the sequence boundaries interpreted on seismic and the depth on cores recovered from holes transecting on the seismic profiles From the interpretation nineteen boundaries were identified U1-U19 these boundaries can be broadly divided into two large units From U19-U11 the upper units it s dominated by downlapped seismic termination pattern along the paleoshelve and truncation surfaces across the shelve edge around site U1351B a number of channel incisions were observed in this profile The lower units from U10-U5 consist of less truncation but more common onlap on paleoshelves it features more drift deposits with sigmoidal reflection pattern The nineteen seismic sequences boundaries correlate perfectly with sharp contacts between sandstone and mud shale on the core sections however few are gradational contacts